Antioxidant Activity and Cytotoxicity Evaluation of New Catechol Hydrazinyl-Thiazole Derivatives as Potential Protectors in Retinal Degenerative Processes - Răzvan-Geo Antemie; Gabriel Marc; Raluca Pele; Ionel Fizeșan; Ionuț-Valentin Creștin; Raluca Borlan; Panagiotis Theodosis-Nobelos; Eleni A. Rekka; Ovidiu Oniga; Ovidiu Crișan; Adrian Pîrnău; Laurian Vlase; et al. (Antioxidants, 2025)
Retinal degenerative processes such as age-related macular degeneration are at the center of many ongoing research studies, as their impact on the general population is significant, with severe visual impairment and even irreversible vision loss if left untreated. Currently, there are few efficient treatments available to stop or limit its progression. In the present paper, a molecular hybridization approach was employed to develop novel compounds that address this issue. By adding either 2-butenal or a β-ionone-derived residue to the hydrazone-catechol-thiazole scaffold, two compounds were designed and synthesized: 5a and 5b. After being characterized by mass spectrometry and nuclear magnetic resonance, and proving potent antioxidant activity in the in vitro assays, the cytotoxicity evaluation using the ARPE-19, BJ, and A549 cell lines revealed a surprisingly low-dose effect of 5a and the unexpected cytotoxic activity of 5b, despite its β-ionone moiety, known for its significant therapeutic properties.